Blood Group Characteristics in Rectal Cancer. A study Conducted in a Tertiary Care Center, Srinagar, Kashmir, India - Abdul Waheed, Dar; Wani, Mansoora; Rasool Gadda, Irfan; Arshad Mustafa, Syed (Asian Pacific Journal of Cancer Care, 2023)
Introduction: Rectal cancer is the third most common cancer in the world. Tumors are most commonly located in the rectosigmoid region. There are many actors in the etiology such as age, geographical features, family history, obesity, diet, and history of malignancy. Blood groups are one of the controversial etiologic factors in CRC. Blood group antigens, covered by Karl Landsteiner in 1901, have been the subject of numerous cancer studies since 1953, when Aird declared that blood group A was associated with stomach cancer. Aim: In the present study, we aimed to determine the effect of blood group characteristics, which play a role in the etiology of Rectal cancer. Method: We Prospectively reviewed the patients who were diagnosed with CRC and operated in our center or at other centers and were followed postoperatively at our centers. Age, gender, histologic TNM stage (tumor, lymph node involvement, and metastasis), tumor-bearing colonRectal segment, ABO blood group, and Rh antigen were examined from the patients’ records. Results: Total of 60 patients with histopathologically confirmed as rectal cancers formed the study population. The male to female ratio in rectal cancers was 1.7:1. The age group varied from 16 to 80 years with most common age group in rectum cancer were between age is 45-64 years constituted (29) 48%. However, we observed relationship in the present study between Rh antigen and lymph node metastasis, liver metastasis, or TNM stage. O Blood group and rh positive was associated with lymph node involvement, higher TNM stage, and also found that risk of liver metastasis. Conclusion: As in Rectal cancer, our findings show that the O (+) blood group is a risk factor in rectal cancers, which have multifactorial etiology. Further genetic studies are needed.